Bending experiment on a novel configuration of cold-formed U-shaped steel-concrete composite beams. (1st February 2019) - Zhou, Xuhong; Zhao, Yi; Liu, Jiepeng; Chen, Yohchia Frank; Yang, Yuanlong
Graphical abstract: Highlights: Novel cold-formed U-shaped steel-concrete composite beam (RCUCB) is studied experimentally. Typical flexural failure was observed in the experiment. RCUCB can achieve plastic bending capacity and excellent deformability due to its monolithic effect. Effective slab width of RCUCB is b + L 0 /3 and design details are suggested accordingly. Bending capacity can be calculated according to the EC4 and JGJ 138 codes. Abstract: This paper discusses a novel configuration of rebar truss stiffened cold-formed U-shaped steel-concrete composite beams (RCUCB). The open steel U-section is stiffened by a rebar truss. The interface between concrete slab and lower part (including steel U-section, encased concrete, and reinforcement) is enhanced with uniformly distributed inverted U-shaped rebars. The reinforcement is installed at the bottom of the lower part to control the concrete longitudinal deformation. A flexural experiment on ten specimens was conducted considering reinforcement ratio, steel ratio, beam depth, and shear stud spacing (at the bottom of steel U-section). Typical flexural failure mode was observed and the rebar truss and inverted U-shaped rebar were found to provide significant integrity for the RCUCB. Thus, the RCUCB can achieve plastic bending capacity and excellent deformability. The mid-span deflection, plastification factor, and ductility factor of the RCUCB are up to L 0 /20, 2.08, and 24, respectively. An effective slab width of b + L 0 /3 may be chosen according to the strain distribution. The bending capacity calculated according to EC4 and JGJ 138-2016 agrees generally well with the test result. Finally, design details pertaining to the width to thickness ratio of bottom steel soffit, the height to thickness ratio of steel web, the transverse reinforcement ratio of concrete slab, and bottom longitudinal reinforcement are suggested accordingly.